Consumer segmentation based on three dimensions of sustainable food consumption: a simultaneous analysis of meat, organic food, and sweet snack purchases based on household panel data in Germany - Schäufele-Elbers, Isabel; Janssen, Meike (Frontiers in Nutrition, 2023)
The literature on sustainable food consumption laments two major gaps: First, the majority of previous studies analyzed consumer behavior based on survey data on consumers’ self-reported behaviors and attitudes. Second, most existing studies focused on one dimension of sustainable food choices. This paper identifies and analyses consumer segments based on the actual purchases of 8,400 households recorded in the GfK household panel data from Germany. We used three indicators of sustainable food consumption behavior: 1) the purchase of organic products as a proxy for the environmental impact of diets, 2) the purchase of meat as a proxy for the climate impact of diets, and 3) the purchase of sweet snacks as a proxy for the healthiness of a diet. The analysis yielded two larger segments with high expenditure shares for one type of unsustainable food (meat/sweet snacks, respectively), two small segments with above average (medium/high) expenditure shares for organic food, and a large ‘mainstream’ segment. The five consumer segments were further analyzed regarding the observed attitude-behavior gap, and the actual prices paid in different product categories. Clear gaps between stated and actual behavior were revealed with interesting differences between the five segments and the three sustainability characteristics. The analysis is a vital starting point for designing a holistic policy instrument mix to close the gaps and to reach a sustainable transformation of the food system.